Protective Role of Activated Protein C against Viral Mimetic Poly(I:C)-Induced Inflammation - Cai, Xiaofeng; Panicker, Sumith R.; Biswas, Indranil; Giri, Hemant; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2021)
Activated protein C (APC) is an anticoagulant plasma serine protease which exhibits potent cytoprotective and anti-inflammatory activities. Here, we studied protective effects of APC on the proinflammatory function of polyinosinic:polycytidylic acid [poly(I:C)], a synthetic analog of viral double-stranded RNA, in cellular and animal models. Poly(I:C) induced histone H3 extranuclear translocation via interaction with toll-like receptor 3 in two established endothelial cell lines. Furthermore, poly(I:C) induced histone H3 extranuclear translocation in J774A.1 macrophages and human neutrophils and formation of macrophage and neutrophil extracellular traps (ETs). Mechanistically, poly(I:C) was found to upregulate expression of peptidylarginine deiminase 4 and enhance its interaction with histone H3, thereby leading to increased histone citrullination and neutrophil ET formation. Poly(I:C) elicited proinflammatory signaling responses by inducing nuclear factor kappa B activation and disrupting endothelial cell permeability. In vivo, poly(I:C) enhanced cell surface expression of Mac-1 on neutrophils in mice and facilitated their infiltration to lung tissues. Poly(I:C) also downregulated thrombomodulin expression in mouse tissues and reduced its circulating soluble level in plasma. We demonstrate in this study that APC and a signaling-selective mutant of APC effectively inhibit proinflammatory signaling effects of poly(I:C) in both cellular and animal models. We further demonstrate that unlike the requirement for endothelial protein C receptor on endothelial cells, the integrin Mac-1 is involved in the protease-activated receptor 1-dependent APC inhibition of macrophage ET formation in J774A.1 cells. Taken together, these results support a key role for APC signaling in inhibiting the viral mimetic-induced proinflammatory signaling responses and histone translocation-associated formation of ETs by innate immune cells.
Keywords: activated protein C; viral mimetic; poly(I:C); inflammation; extracellular traps